Hemorrhagic syndrome at liver cirrhosis - I. A. Kurkina; O. S. Volkova; M. V. Mayevskaya; V. T. Ivashkin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To demonstrate different points of view on hemorrhagic complications in patients with liver cirrhosis (LC), relation of these complications to disorders of hemostatic system.Key points. Physiology of hemostatic system is intimately related to liver function because parenchymatous cells produce the majority of coagulating and fibrinolytic systems factors. Hence, chronic or acute diseases of this organ frequently have profound effect the system of hemostasis. Bleeding developing at invasive procedures in LC patients, bleeding from varicose esophageal veins, hematomas, hemorrhagic purpura, nasal bleeding, odontorrhagia, menorrhagias are actual clinical problems. Laboratory diagnostics of disorders in «hemostasisfibrinolysis» system in patients with the LC underwent essential changes at the last decade. Standard complex tests for hemostasis lose their diagnostic value in this group of patients. Active search of the laboratory methods is conducted, allowing to estimate the risk of bleeding in liver cirrhosis patients. Strategy in treatment of hemorrhagic complications in LC is directed on prevention of pending bleedings and well-timed onset of medical actions in the case of its development. Basic principles of therapy are: application of erythrocytes, plasma, platelets concentrate, recombinant factor VIIa, concentrates of prothrombin complex, desmopressin, antifibrinolytic drugs, thrombo-and erythropoietin, antibiotics. The relation to prescription of components of blood is cautious now, there are no definite indications to their application and criteria of efficacy.Conclusion. The problem of prediction of hemorrhagic complications in patients with LC by modern laboratory tests remains open. There is no conventional strategy of treatment and prophylaxis of bleedings for these patients. Carrying out of randomized controlled studies for evaluation of laboratory tests in prediction of bleedings or thromboses at patients with cirrhoses, for studying efficacy of modern concentrates of factors of coagulation, for assessment of restrictive policy of decantation of blood components is necessary.